Amphiphilic NaY zeolite particles loaded with niobic acid: Materials with applications for catalysis in immiscible liquid-liquid system - Nur, Hadi; Ikeda, Shigeru; Ohtani, Bunsho (AkadÃ©miai KiadÃ³, Budapest., 2004)
The catalytic potential of catalysts for acid-catalyzed reactions has been demonstrated by NaY zeolite loaded with alkylsilane-covered niobic acid in the liquid phase hydration of 1,2-epoxyoctane with water. The catalytic activity of the catalysts was correlated to the amphiphilic character of the solid catalyst particles